Go Green Around Campus: Environmental Management Collaboration With the Household Waste Disposal Association - Karmanah; Nia Sonani; Abdul Rahman Rusli; Dewi Fitrianti (Almufi Jurnal Pengabdian Kepada Masyarakat, 2022)
Environmental management related to the handling of household waste in the RW 08 area is still shared homework. If not managed properly, the increasing number will cause problems, including environmental pollution, and affect public health problems. One of the efforts to reduce waste generation at Temporary and final Waste Disposal Sites, a Community Service activity (PKM), is carried out "Go Green Campus Circle: Environmental Management Collaboration with the Household Waste Disposal Association ."Through deliberation approaches, counseling, training, mentoring, and collaboration in waste management activities, the activity method is through deliberation. This activity is carried out by collaborating with the garbage disposal association, RW management, Kelurahan, and local government to deal with the Kukutu TDS's environmental management and sustainably manage household waste. The activity results showed a very good response from waste managers, RW administrators, Kelurahan, and Regional Governments during the implementation of PKM activities. Likewise, the youth waste management response was enthusiastic about participating in counseling and training on waste management and maggot cultivation. Furthermore, the community's response around the TDS, posyandu cadres, and PKK cadres when attending counseling and training on making handicrafts made from inorganic waste showed a good answer. Activities that receive funding assistance for the independent policy research program to study independent campuses and community service based on research results and prototype PTS Ditjen Diktiristek This 2021 fiscal year can increase public awareness and waste management in handling household waste. In addition, the establishment of collaboration in environmental management between communities and local governments reduces the impact of environmental pollution.